2005
DOI: 10.1111/j.1600-6143.2005.00921.x
|View full text |Cite
|
Sign up to set email alerts
|

Patient Survival Following Renal Transplant Failure in Canada

Abstract: Studies from the United States have shown that renal allograft failure is associated with a high mortality rate. The purpose of this study was to determine whether transplant failure was associated with survival in a recent cohort of kidney transplant recipients with different characteristics and a distinct health care system from the United States. Cox regression was used to model allograft loss as a time-dependent variable with patient survival as the primary outcome in 4743 kidney transplant recipients from… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
61
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(65 citation statements)
references
References 25 publications
3
61
0
1
Order By: Relevance
“…Our observation is in line with the findings of former cohorts studying this question [3,4,5,6,7,8]. …”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Our observation is in line with the findings of former cohorts studying this question [3,4,5,6,7,8]. …”
Section: Discussionsupporting
confidence: 82%
“…A number of recent studies have shown that the mortality rate in this population is higher than among age-matched incident dialysis patients, patients listed for primary transplantation, and patients with a functioning transplant [2]. Five former cohorts did not find a significant difference in mortality between patients starting dialysis with graft failure (GF) and transplant naive patients on dialysis treatment (HD) [3,4,5,6,7,8]. There is no clear indication about the optimal timing for starting dialysis after graft failure.…”
Section: Introductionmentioning
confidence: 99%
“…Crude death rates of US dialysis patients after renal allograft loss exceed that of patients on the kidney transplantation waiting list, 4,5 and high mortality rates after allograft loss have also been observed in Canadian registries. 6 Repeat transplantation is associated with improved survival among patients with failed renal allografts, 4 but only approximately 15% of these patients undergo repeat transplantation. 4 Thus, optimal treatment of the large majority of these patients who do not receive repeat kidney transplantation is a challenging problem.…”
mentioning
confidence: 99%
“…Others have contended that the failed allograft is a source of sepsis (4) or chronic inflammation that may lead to complications such as erythropoietin resistance (8), and therefore, should be routinely removed. The high rate of morbidity and mortality among the transplant failure population has been highlighted in a number of recent publications (16)(17)(18)(19)(20)(21)), yet there is relatively little known about the factors that contribute to the poor outcomes of this population. The impact of the retained failed allograft on the health of transplant failure patients is unknown, and warrants examination because the failed graft could be removed if shown to be harmful.…”
Section: Introductionmentioning
confidence: 99%